Dynamics of Cancer- and Immune-Pathway Gene Expression During Colitis and Recovery from Gut Injury in Mice Fed the Total Western Diet. (29th May 2020) - Rodriguez, Daphne; Neil, Canyon; Armburst, Tess; Garg, Gauri; Hintze, Korry; Pestka, James; Benninghoff, Abby
Abstract: Objectives: Consumption of a Western type diet is a known risk factor for colorectal cancer. Our group previously developed the total Western diet (TWD) for rodents with energy and nutrient profiles that emulate a typical Western diet. In prior studies, consumption of the TWD in C57BL6/J mice markedly enhanced gut inflammation and colon tumorigenesis.  In this study, our objective was to assess the dynamics of immune and cancer pathway gene expression during the onset and resolution of DSS-induced colitis. Methods: Male C57BL/6 J mice were fed the standard AIN93G diet or the TWD diet for 45 days; on day 21, mice were provided 1% (w/V) DSS in the drinking water for 10 days. On days 33 and 45, the colitis disease activity index was determined.  Also, days 21, 33, and 45, colon mucosa was collected (n = 8 per group) and total mRNA was isolated for gene expression analysis using the NanoString nCounter Mouse PanCancer Immune Profiling Panel, which targets 750 cancer- and immune-related genes. Results: Results of these targeted gene expression analyses point to striking up-regulation of hundreds of genes associated with interferon response, inflammation, innate immunity, adaptive immunity, and chemokines and receptor pathways in mice fed TWD as compared to the standard AIN diet during active colitis. In a pattern that mirrored the persistent elevation in inflammation and mucosal injury observed in our prior longitudinal studies with TWD and DSS exposure, dysregulation of many of these genes persisted through recovery from gut injury, in addition to the stimulation of other pathways, such as B-cell activation and antigen processing. Conclusions: This study is the first to assess the dynamics of immune and cancer pathway gene expression during the onset and resolution of DSS-induced colitis and the first to employ highly multiplexed, direct digital detection NanoString technology for analysis of a colitis transcriptome in mouse colon mucosa. Our observations indicate that consumption of the TWD markedly enhanced colitis, delayed recovery from gut injury, and enhanced colon tumorigenesis likely via extensive changes in expression of immune-related genes in the colon mucosa. Funding Sources: Supported by the Hatch Capacity Project from the USDA National Institute of Food and Agriculture and the Dr. Robert and Carol Deibel Family Endowment.